Novel microbiota Mesosutterella faecium sp. nov. has a protective effect against inflammatory bowel disease - Yu, Seung Yeob; Oh, Byeong Seob; Ryu, Seoung Woo; Bak, Jeong Eun; Heo, Eun Seo; Moon, Jeong Chan; Jeong, Jae-Ho; Lee, Ju Huck (Frontiers in Microbiology, 2024)
A novel Gram-negative, obligate anaerobe, non-motile, flagella-lacking, catalase- and oxidase-negative, coccobacilli-shaped bacterial strain designated AGMB02718T was isolated from swine feces. The 16S rRNA gene analysis indicated that strain AGMB02718T belonged to the genus Mesosutterella with the highest similarity to M. multiformis 4NBBH2T (= DSM 106860T) (sequence similarity of 96.2%), forming a distinct phylogenetic lineage. Its growth occurred at 25–45°C (optimal 37°C) and in 0.5–1% NaCl (optimal 0.5%). Strain AGMB02718T was asaccharolytic and contained menaquinone 6 (MK-6) and methylmenaquinone 6 (MMK-6) as the predominant respiratory quinones. The major cellular fatty acids in the isolate were C18:1ω9c and C16:0. Based on the whole-genome sequencing analysis, strain AGMB02718T had a 2,606,253 bp circular chromosome with a G + C content of 62.2%. The average nucleotide identity value between strain AGMB02718T and M. multiformis 4NBBH2T was 72.1%, while the digital DNA–DNA hybridization value was 20.9%. Interestingly, genome analysis suggested that strain AGMB02718T possessed a low-toxicity lipopolysaccharide (LPS) because the genome of the isolate does not include lpxJ and lpxM genes for Kdo2-Lipid A (KLA) assembly, which confers high toxicity to LPS. Moreover, in vitro macrophage stimulation assay confirmed that AGMB02718T produced LPS with low toxicity. Because the low-toxicity LPS produced by the Sutterellaceae family is involved in regulating host immunity and low-toxicity LPS-producing strains can help maintain host immune homeostasis, we evaluated the anti-inflammatory activity of strain AGMB02718T against inflammatory bowel disease (IBD). As a result, strain AGMB02718T was able to prevent the inflammatory response in a dextran sulfate sodium (DSS)-induced colitis model. Therefore, this strain represents a novel species of Mesosutterella that has a protective effect against DSS-induced colitis, and the proposed name is Mesosutterella faecium sp. nov. The type strain is AGMB02718T (=GDMCC 1.2717T = KCTC 25541T).